Chemical functionalization of low-buckled SiGe monolayer: Effects on the electronic and magnetic properties. (1st November 2022) - Nguyen, Duy Khanh; Guerrero-Sanchez, J.; Rivas-Silva, J.F.; Vu, Tuan V.; Cocoletzi, Gregorio H.; Hoat, D.M.
Abstract: Surface modification has been widely employed to modify fundamental properties of two-dimensional (2D) materials and create new multifunctional candidates for practical applications. In this work, the effects of chemical functionalization on silicon germanide (SiGe) monolayer have been investigated using first-principles calculations. Pristine monolayer exhibits good dynamical stability and a Dirac cone at K point in the band structure. The nearly semimetallic nature and absence of magnetic properties represent great challenge for SiGe monolayer applications. Our results show that these deficiencies can be overcome with oxygenation and hydrogenation processes. Oxygen (O) and hydrogen (H) atoms prefer to be adsorbed on-top of bridge and Si atom, respectively. The non magnetic nature is preserved under oxygenation, however a significant band gap up to 1.35 eV can be introduced depending on the O concentration. Meanwhile, the ferromagnetic semiconducting is induced by hydrogenation, where magnetic properties are produced mainly by Ge atoms, regardless the H coverage. In fact, efficient methods have been introduced to make SiGe monolayer promising 2D material for optoelectronic and spintronic applications through adsorbing O and H atoms.